Theoretical Substantiation of the Parameters of a Complex Device for Softening a Rail Track with a Rectifier - A.O.Nauryzbayev; B.K.Utepbergenov; B.N.Ramazanov; J.I.Turmambetov (Genius Journals, 2023)
This article found that to ensure high quality of work and energy efficiency, the traces formed by tractor wheels during grinding are mitigated by the use of swept claws and their parameters are in the range of the angle of entry into the ground within 0 20 26 − , the angle of sharpening within 0 36 44 − , the angle of wing opening 0 60 , the angle of blade sharpening within 0 12 15 − , it was determined that the width the coverage should be 47 cm when using one working body and 26 cm when using two working bodies.
Keywords: Leveler; rectifier; track softener; softener paw